Spectroscopic and Microscopic Studies of Archaeological Celadons Recently Excaveted From Alagankulam, Tamilnadu, India - G. Velraj, P. Sathya (Recent Research in Science and Technology, 2010)
Ceramics are the most common archaeological material used by the historians to draw chronological and cultural characterizations. Among these, porcelains and celadons are recognized as good historical relics. Moreover, the different facets of science, technology and culture are also imprinted in these samples. Hence, the knowledge of microstructures, compositions and technologies used can be helpful in identifying and dating the ancient artifacts. In this paper,Ã‚Â three representative celadon samples found in the course of archaeological excavations at the site Alagankulam, Ramanathapuram District, Tamilnadu, India were investigated by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) in order toÃ‚Â achieve their mineralogy and chemical behavior. X-ray diffraction was used to accomplish possible crystalline mineral phases within the clays that composed of samples.Ã‚Â On the other hand, FT-IR studies helped in identifying the different mineral assemblages from the tentative vibrational assignments of absorption bands. Microstructure and one or multi step firings can be inferred from the SEM.